1996
DOI: 10.1021/tx950146p
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 3,4-Estrone Quinone with Mimics of Amino Acid Side Chains

Abstract: Reaction of 3,4-estrone o-quinone (3,4-EQ) with several amino acid side chain mimics, including 4-ethylphenol, 4-methylimidazole, acetic acid, and propanethiol, gave a mixture of several products including the catechol, Michael addition products, and dimeric products of the catechol. On the other hand, several other amino acid side chain mimics, including ethanol, acetamide, 1-ethylguanidine, and 3-methylindole, did not result in any addition products or catechol formation. Michael addition to 3,4-EQ with 4-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
6
17
0
Order By: Relevance
“…Several unpolar and partially resolved compounds were detected at the end of the gradient (R t 45-50 min). They corresponded to previously described covalently dimeric forms 31,32 of E-2,3-Q (not indicated by UV detection, Fig. 3a), evidenced by their respective MS-MS spectra (data not shown).…”
Section: Reaction Between E-23-q and DCsupporting
confidence: 86%
“…Several unpolar and partially resolved compounds were detected at the end of the gradient (R t 45-50 min). They corresponded to previously described covalently dimeric forms 31,32 of E-2,3-Q (not indicated by UV detection, Fig. 3a), evidenced by their respective MS-MS spectra (data not shown).…”
Section: Reaction Between E-23-q and DCsupporting
confidence: 86%
“…The labile estrogen quinones readily react with a variety of physiologic compounds, ranging from amino acids, such as lysine and cysteine, to the tripeptide glutathione (g-glutamyl-L-cysteinylglycine), as well as fatty acids and other lipids, and nucleic acids and DNA (17,(35)(36)(37)(38). In these reactions, the quinones form Michael addition products with nucleophilic groups, typically yielding a mixture of several stable conjugation products (39,40). In view of this reactivity, one can postulate that the substrate recognition site of CYP1B1, which is in contact with E 2 -3,4-Q or E 2 -2,3-Q, does not contain lysine or cysteine residues as these amino acids would be attacked by the quinones.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Abul-Hajj et al, 1996;Iverson et al, 1996) on the reactivity of o-quinone have demonstrated that attack of nucleophiles presented the hard and soft acid and bases (HSAB) theory (Pearson, 1973); that is, 1,4 Michael addition for oxo and amino groups and 1,6 Michael addition for thio groups. The high cytotoxic activity of DBP may be responsible for the formation of o-quinone of this compound.…”
Section: Figmentioning
confidence: 99%